2022
DOI: 10.2147/ott.s358008
|View full text |Cite
|
Sign up to set email alerts
|

CDKN3 Overcomes Bladder Cancer Cisplatin Resistance via LDHA-Dependent Glycolysis Reprogramming

Abstract: Background Aerobic glycolysis plays an important role in bladder cancer (BLCA) progression and chemoresistance. Cyclin-dependent kinase inhibitor-3 (CDKN3), a dual-specificity protein tyrosine phosphatase, has aberrant upregulation in multiple cancer types and is associated with tumorigenesis. However, the role of CDKN3 in BLCA progression and glycolysis has not been elucidated. Purpose In this study, we investigated the effect and underlying mechanisms of CDKN3 on blad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Although the main role of CDKN3 is to inhibit the progression of the cell cycle, it is overexpressed in many types of malignancies such as gastric cancer, prostate cancer, hepatocellular, cervical, breast, and epithelial ovarian cancers which was in concomitant with expression pan-cancer analysis conducted. [18,[39][40][41][42] Overexpression of CDKN3 in these malignancies is associated with inadequate prognosis, while CDKN3 in glioblastomas is considered a tumor suppressor gene. A study showed that CDKN3 prevents aneuploidy and it performs the complex task of managing cell division through a combination of direct pathways that involve regulating the SAC and the mitotic clock, as well as indirect mechanisms that involve preserving the integrity of centrosomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the main role of CDKN3 is to inhibit the progression of the cell cycle, it is overexpressed in many types of malignancies such as gastric cancer, prostate cancer, hepatocellular, cervical, breast, and epithelial ovarian cancers which was in concomitant with expression pan-cancer analysis conducted. [18,[39][40][41][42] Overexpression of CDKN3 in these malignancies is associated with inadequate prognosis, while CDKN3 in glioblastomas is considered a tumor suppressor gene. A study showed that CDKN3 prevents aneuploidy and it performs the complex task of managing cell division through a combination of direct pathways that involve regulating the SAC and the mitotic clock, as well as indirect mechanisms that involve preserving the integrity of centrosomes.…”
Section: Discussionmentioning
confidence: 99%
“…[40] Another finding about CDKN3 involvement in cisplatin resistance in BLC showed that CDKN3 altered/inhibited GC chemoresistance in BLC cell lines. [39] GSEA identified a negatively enriched ACACTGG, MIR-199A, and MIR-199B to be affected by CDKN3 upregulation. The relationship between CDKN3 and miRNA is very well understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human CDKN3 gene encodes cyclin-dependent kinase inhibitor 3, which is a bispecific protein tyrosine phosphatase of the CDC14 group. CDKN3 is used as CDK1 and CDK2 inhibitory proteins, which are conventionally considered a negative regulatory factor of the cell cycle process ( Li et al, 2022 ). Although CDKN3 has a negative adjustment effect on CDK1 and CDK2, the carcinogenic effect of CDKN3 is abnormally expressed, which is related to a variety of human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CDKN3 has been implicated in tumor progression. Studies have established a notable upregulation of CDKN3 in lung cancer [ 16 ], gastric cancer [ 17 ] and breast cancer [ 18 ] correlating significantly with poor patient prognosis. Subsequent investigations have validated that CDKN3 exerts influence on the drug resistance of bladder cancer cells by disrupting glycolysis, thereby impacting metabolic reprogramming [ 19 ].…”
Section: Introductionmentioning
confidence: 99%